Analysis of the Internal Marketing Dimensions in Social Economy Organizations: Study Applied to Co-operativism in Ecuador - González Santa Cruz, Francisco; Moreira Mero, Nelly; Loor Alcívar, María Iliana; Hidalgo Fernández, Amalia (Frontiers in Psychology, 2020)
Internal marketing involves the development of organisational strategies that promote the welfare of the employees who, in turn, play a transcendental role in achieving institutional goals. Ecuadoran co-operativism lacks relevant studies of this construct and, because of this, this research intends to analyse the dimensions of internal marketing, through the validation of a measuring instrument that has been adapted to this sector of the social economy, in a developing country. The methodology is based on the completion of field work, where a structured questionnaire for a representative sample of 2,499 employees and officers of the operatives of Ecuador was applied. The suitability of the scale was determined through the means of a model of Ecuadoran structural equations. The results show that internal marketing is a multi-dimensional construct and it can be measured in six dimensions: identify Value Exchange, internal market segmentation, internal communication, management concern, training and work/family balance.